2003
DOI: 10.1111/j.1365-2621.2003.tb07048.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Endogenous Proteases and Transglutaminase on Thermal Gelation of Salted Squid Muscle Paste

Abstract: Thermal gelation of salted squid mantle muscle paste was studied in relation to endogenous proteases and transglutaminase. Myosin in the paste was preferentially degraded into 130-kDa and 90-kDa fragments at an optimum temperature of 30°C. Degradation was inhibited with EDTA or 1,10-phenanthroline, suggesting the presence of metalloproteases. Myosin degradation was markedly reduced above 40°C. Although 10 mM Ca 2+ increased cross-linking of myosin heavy chains by activating the endogenous transglutaminase, set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…These changes are caused by many kinds of enzymes such as proteases present in squid. Although several researchers have reported the presence of metalloproteinases that cleave myosin into heavy and light meromyosin (Konno and Fukazawa 1993; Okamoto and others 1993) and affect thermal gelation of squid muscle paste (Park and others 2003; Tujioka and others 2005), the protease involved in shiokara production has been investigated in only one study. Cathepsin B‐ and L‐like proteases present in squid liver participate in muscle tenderization through the degradation of myofibrils (Makinodan and others 1993).…”
Section: Introductionmentioning
confidence: 99%
“…These changes are caused by many kinds of enzymes such as proteases present in squid. Although several researchers have reported the presence of metalloproteinases that cleave myosin into heavy and light meromyosin (Konno and Fukazawa 1993; Okamoto and others 1993) and affect thermal gelation of squid muscle paste (Park and others 2003; Tujioka and others 2005), the protease involved in shiokara production has been investigated in only one study. Cathepsin B‐ and L‐like proteases present in squid liver participate in muscle tenderization through the degradation of myofibrils (Makinodan and others 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the microstructure of myofibrils 10) and in SDS-polyacrylamide gel electrophoretic patterns of whole muscle proteins 11) were examined previously in heated squid muscle, but there have been no reports concerning with actin liberation and the responsible factor.…”
mentioning
confidence: 99%
“…A high degree of protein aggregation is mediated by transglutaminase activity [12]. Microbial transglutaminase activated the crosslinking of MHC [23], which is one of the factors involved in the gelation of kamaboko [24]. Because the optimum temperature of microbial transglutaminase is 50°C [25], protein aggregation occurring in suwari gel set at 30°C was slower than that of gels set at 40 and 50°C.…”
Section: Discussionmentioning
confidence: 91%
“…There are several reports that revealed that the absence of MHC bands and the presence of polymer bands were [23,26,27]. During setting, crosslinking of myosin was established and led to MHC band reduction and polymer band increase, as revealed by SDS-PAGE analysis.…”
Section: Discussionmentioning
confidence: 95%